IMPLEMENTATION OF SMART CITY APPLICATION IN SUSTAINABLE TRANSPORT SYSTEMS: PROSPECTS AND DEVELOPMENT OF SMARTCITY IN INDONESIA - Danarti Karsono; Muhammad Rizal Fernandita Pamungkas, Moh. Erkamim, A. Bamban Yuuwono (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
The study aims to discuss the prospects and development of the Smart City concept in sustainable transportation systems in Indonesia. The study assesses the various challenges and opportunities emerging from the integration of information and communication technology into existing transport infrastructure. Through an in-depth literature exploration, the research identifies key factors that influence the implementation of Smart Cities and explores strategies that can accelerate the realization of efficient, inclusive, and sustainable smart transport. Research results show that the implementation of Smart Cities in Indonesia is still in its early stages, but has great potential due to the demands of rapid urbanization and development. The Smart City concept is expected to support reducing congestion, improving energy efficiency, and reducing greenhouse gas emissions. However, the research also reveals a number of major obstacles, including the need for massive investment in infrastructure, cyber security, and the digital gap between regions.